Recognizing and Implementing International Human Rights Standards in Domestic Legislation: An Exposure Under Ukrainian Law - Serohin, Vitalii Oleksandrovych; Serohina, Svitlana Hryhorivna; Gryshko, Liliya Mykolayivna; Danicheva, Kateryna Petrivna (Universidad Hemisferios, 2021)
Everything about human right is inalienable void of violation from the human race. It is therefore that responsibility of the international community in ensuring the effective preservation and respect of these rights without any threat of violations. In ensuring its recognition and implementation, international standards have been established where there is the need of States parties to these international human right treaties in ensuring its incorporation in its various domestic legislations. The content and specific features of the introduction of international human rights standards into national legislation have been analyzed in the article. The methodological basis of research is a set of general scientific and special methods, in particular, dialectical, historical-legal, epistemological, comparative-legal. International standards for the protection of human rights have been defined as principles and norms enshrined in international regulatory legal acts that define fundamental human rights and freedoms, the obligation of the State to respect them, to assist in their realization, preservation and protection against unlawful encroachments, and to establish liability for their violations and methods of protection. It has been clarified that the procedure of implementation of international human rights standards into national legislation includes the following stages: (i) recognition of human rights by the State and their enshrinement in national legislation; (ii) institutionalization of the standard of human rights protection; (iii) bringing the current legislation in line with the international human rights standard and interpreting the latter; (iv) establishment of measures and means of protection and defense of human rights; (v) determining the procedure for the realization of the enshrined right; (vi) control over the observance of the international human rights standard.